A Framework for Automated and Composable Testing of Component-Based Services (2014)
The vision of service-oriented computing has been largely developed on the fundamental principle of building systems by composing and orchestrating services in their control flow. Nowadays, software development is notably influenced by service-oriented architectures (SOAs), in which the quality of software systems is determined by the quality of the involved services and their actual composition. Despite the efforts on improving their individual quality, adding or replacing services in an evolving system can introduce failures, thus compromising the satisfaction of the system's functional and extra-functional requirements. These failures erode the trust in the SOA vision. Thus, a key issue for the industrial adoption of SOA is providing service providers, integrators, and consumers the means to build confidence that services behave according to the contracted quality conditions. In this paper we present a first version of PA SCA NI, a framework for specifying and executing test specifications for service-oriented systems.